ACCESS TO COMMUNITY-BASED SOCIAL SERVICES AMONG OLDER ADULTS IN VIETNAM: EVIDENCE FROM HANOI, QUANG NINH, AND YEN BAI - Lien, Nguyen Thi (Veredas do Direito, 2026)
Population ageing has become a major demographic trend in many countries, including Vietnam. As the number of older adults continues to increase, access to community-based social services plays an increasingly important role in supporting their health, well-being, and social participation. This study examines the accessibility of community-based social services among older adults and identifies the barriers that affect service utilization. A cross-sectional survey was conducted with 360 older adults aged 60 years and above in three provinces in Vietnam: Hanoi, Quang Ninh, and Yen Bai. Data were collected using structured questionnaires and analyzed using descriptive statistical methods. The study examined socio-demographic characteristics of respondents, types of social services accessed, and barriers to service accessibility. The findings show that health care services were the most commonly accessed services among older adults, followed by recreational activities and religious or spiritual services. However, access to other social services such as psychological counseling, legal consultation, and employment support remained relatively limited. Several barriers were identified, including lack of information about services, financial constraints, limited service availability, and mobility limitations. The study highlights the importance of strengthening community-based social service systems to better support the needs of older adults. Policy efforts should focus on improving service availability, enhancing information dissemination, and reducing structural barriers that limit access to services.